Diary of a wimpy kid : old school - Kinney, Jeff. (2015)
"Life was better in the old days. Or was it? That's the question Greg Heffley is asking as his town voluntarily unplugs and goes electronics-free. But modern life has its conveniences, and Greg isn't cut out for an old-fashioned world. With tension building inside and outside the Heffley home, will Greg find a way to survive?"--
Keywords: Electronics -- Fiction; Family life -- Fiction; Diaries -- Fiction; Humorous stories; JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / Comics & Graphic Novels / General